1999
DOI: 10.1111/j.1540-8159.1999.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ischemia on P Wave Dispersion and Maximum P Wave Duration During Spontaneous Anginal Episodes

Abstract: P wave dispersion (P dispersion), defined as the difference between the maximum and the minimum P wave duration, and maximum P wave duration (P maximum) are electrocardiographic (ECG) markers that have been used to evaluate the discontinuous propagation of sinus impulses and the prolongation of atrial conduction time, respectively. To study the effects of myocardial ischemia on P dispersion and P maximum, 95 patients with coronary artery disease (CAD) and typical angina pectoris and 15 controls with angina lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 33 publications
2
91
1
2
Order By: Relevance
“…Higher Pd on the surface ECG is thought to reflect the heterogeneity of structural and electrophysiologic properties of atrial myocardium and inhomogeneous propagation of atrial impulse which predisposes to reentry. 20 Dilaveris et al 11,12,15 studied Pd in patients with idiopathic PAF, with coronary artery disease and spontaneous angina, and with hypertension separately. Authors have shown higher dispersion of P wave in patients who developed AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher Pd on the surface ECG is thought to reflect the heterogeneity of structural and electrophysiologic properties of atrial myocardium and inhomogeneous propagation of atrial impulse which predisposes to reentry. 20 Dilaveris et al 11,12,15 studied Pd in patients with idiopathic PAF, with coronary artery disease and spontaneous angina, and with hypertension separately. Authors have shown higher dispersion of P wave in patients who developed AF.…”
Section: Discussionmentioning
confidence: 99%
“…10 Alterations of P-wave duration have been studied in several clinical settings, such as idiopathic PAF, ischemic heart diseases, after coronary artery bypass surgery, hypertension, and congestive heart failure. [11][12][13][14][15][16] Recently, P-wave dispersion (Pd) has been proposed to be a useful index for identifying the risk for AF in several clinical conditions. 11,15 Thus, in the present study, we investigated whether Pd could be used to discriminate between patients with HCM with and without a history of PAF.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızın sonucunda pozitif miyokart perfüzyon sintigrafisi sonucuna artmış P dalga dispersiyonun eklenmesinin tıkayıcı KAH varlığını saptamada testin özgüllüğünü ve duyarlılığını anlamlı olarak artırdığını ve KAH yaygınlığı ile de anlamlı bir ilişki içerisinde olduğunu saptadık. Miyokart iskemisinin sol ventrikül ve sol atriyal basınçlarda artışa yol açtığı ve bu durumun P dalga süresi ve dispersiyonunda uzama meydana getirebileceği düşünüldüğünde, P dalga süresi-nin koroner anjiyografi öncesi risk sınıflandırılmasında kullanıl-ması uygun bir yaklaşım gibi görülmektedir (14) .…”
Section: Discussionunclassified
“…An increase in this parameter was also observed in patients with a diastolic dysfunction; however, the increase was not in proportion to the severity of the disease (8). The speed of the impulse conduction in the myocardium depends on the activity of the immune system and the presence of ischaemia (4,6). Additional factors that can increase P d and that should be taken into account while interpreting results related with atrial conduction include endocrine disease, such as diabetes, thyroid hyperfunction, and the terminal stadium of renal failure (2,5,10,(21)(22)(23)25).…”
Section: Discussionmentioning
confidence: 99%